Impact of perceived internal respect on flourishing: A sequential mediation of organizational identification and energy - Ghulam Abid; Shazaf Ijaz; Tahira Butt; Saira Farooqi; Maryam Rehmat (Cogent Business & Management, 2018)
Employee flourishing has engrossed significant attention in recent times due to the positive consequences for both workers and employers. Every organization desires that their employees are motivated, enthusiastic, passionate and committed to their organization as well as to their organizational tasks. It is important for organization that they must create a respectful atmosphere to run their operations efficiently and effectively because respect is the vital factor through which employees can perform better and feel satisfied. Despite immense work in this field, there is less research on the antecedents of flourishing. Drawing on self-determination theory and broaden-and-build theory, our study examines the indirect influence of perceived internal respect (PIR) on employee's flourishing. Moreover, we also investigated the sequential mediating mechanism of organizational identification and energy in the relationship between PIR and flourishing of employees. Data were collected in two-wave cross-sectional time horizon. The results were obtained by using PROCESS macro by Hayes on actual sample of 250 employees from various job functions. The results indicated strong empirical support for all the direct and indirect hypothesized relationships. The finding of the study contributes to the better understanding of the most emerging construct, namely, employee flourishing. Theoretical and practical implications are also discussed in the light of findings.
Keywords: 650